Does demographic backgrounds affect agricultural drone technology in granary areas? - Muhammad Khalil, Nur Ieffah; Man, Norsida; Ramli, Nurul Nadia (RSIS International, 2024)
The adoption of technology in paddy sector appears to have coincided with the advancement of the country's development, as the agricultural sector is likewise undergoing the Industrial Revolution 4. Over the years, the Malaysian rice production system has faced a number of challenges, including extreme weather conditions, poor soil fertility and nutrient management, farmers' lack of awareness and knowledge, reluctance to use genetically modified planting materials, and poor technology deployment. Despite the adoption of drone in the paddy farming is seem gradually increasing, the factor effecting the adoption remains unclear. Thus, this study investigates the association between socio-demographic profiles and their adoption towards drone technology in selected granary areas. A cross-sectional study was conducted among 384 paddy farmers using a self-administered questionnaire, selected through cluster random sampling. Result found that there are no association between age, education level, experience, farm size and income. The finding recommend that government should provide opportunities for all paddy farmers regardless their background in adopting drone technology to improve the modernization in paddy industry.